2016
DOI: 10.1007/s10096-016-2585-0
|View full text |Cite
|
Sign up to set email alerts
|

Influenza 2014–2015 among pregnant Japanese women: primiparous vs multiparous women

Abstract: Objectives: This study was performed to determine whether multiparous pregnant women are prone to influenza. Methods:A questionnaire survey was conducted at 19 centres located throughout Japan, targeting all 6694 postpartum women within 7 days after birth before leaving the hospital. All women gave birth during the study period between March 1, 2015, and July 31, 2015. Data regarding vaccination and influenza infection in or after October 2014, age, previous experience of childbirth, and number and ages of coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…In a study by Yamada et al in Japan, multiparous women had a higher risk of influenza regardless of vaccination status than primiparous women (20). Likewise, in the present study, we found that parity was a significant factor affecting the consequence of influenza during pregnancy.…”
Section: Discussionsupporting
confidence: 81%
“…In a study by Yamada et al in Japan, multiparous women had a higher risk of influenza regardless of vaccination status than primiparous women (20). Likewise, in the present study, we found that parity was a significant factor affecting the consequence of influenza during pregnancy.…”
Section: Discussionsupporting
confidence: 81%
“…Yamada et al reported that the vaccination coverage of pregnant women was approximately 50% in the 2013-2014 and 2014-2015 influenza seasons in Japan. 11,12 In the current study, approximately half of pregnant women (53.5% in 2017 and 47.4% in 2018) were vaccinated for seasonal influenza. Although the influenza vaccination is voluntary and not a routine vaccination, most pregnant women surveyed knew that the influenza vaccination was available for pregnant women in Japan.…”
Section: Discussionmentioning
confidence: 77%
“…However, the proportional influenza vaccine uptake was similar to that reported in a previous study. 11,12 Third, although the questionnaire in the current study included 10 questions, there are many factors that could potentially influence vaccine uptake. We focused on the key individuals who provided information via their recommendations in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-world evidence on the prevalence of HRC in the elderly was not available; for this reason, consistency between estimates was assured by applying the age-dependent increase of HRC prevalence based on a JammNet database analysis and the published literature. Additional sources were needed to retrieve data for two highrisk groups that were not covered in JammNet: women 2 weeks postpartum and residents of long-term care facilities [17][18][19][20] . The ratio of the elderly with HRC to adults with HRC was 2.55, and the prevalence of HRC in the elderly was estimated at 49%.…”
Section: Population Characteristicsmentioning
confidence: 99%